Closed suction drainages in Lower Limb Joint Arthroplasty: A level I evidence based meta-analysis. Issue 3 (June 2022) - Migliorini, Filippo; Maffulli, Nicola; Betsch, Marcel; Eschweiler, Jörg; Tingart, Markus; Baroncini, Alice
Abstract: Introduction: The role of closed suction drainage during elective total joint arthroplasty is still unclear. The present study compared the use of closed suction drains to no drainage for elective total knee arthroplasty (TKA) and in total hip arthroplasty (THA) through a meta-analysis of randomized clinical trials (RCTs). Methods: Following the PRISMA guidelines, a meta-analysis of randomized controlled trials identified in December 2021. All randomized clinical trials comparing the use of closed suction drains to no drainage for elective THA or TKA were considered. Results: Twenty-five RCTs were included in the final analysis. 49% (1722 of 3505) of patients received no-drainage, and 51% (1783 of 3505) received closed suction drainage. There was no evidence of a statistically significant evidence between the two groups in occurrence of postoperative infections (P = 0.4), mean total postoperative hemoglobin (P = 0.2) or length of hospital stay (P = 0.1). The no-drainage group showed a lower rate of blood transfusion (P < 0.0001). Conclusion: There is no evidence to support the routine use of closed suction drainage in THA or TKA patients. Level of evidence: Level I, meta-analysis of randomized clinical trials. Highlights: The role of closed suction drainage during elective total joint arthroplasty is still controversial The purpose of closed suction drainage is to prevent post-operative ematomas. However, increased blood loss, reduced tamponade effect, constant monitoring from healthcare personnel, retrograde migration of bacteria are potential risk related to the drainage. The present meta-analysis of RCTs showed no evidence in support of the routine use of closed suction drainage during elective THA and TKA.